2007
DOI: 10.3892/ijmm.20.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins play a crucial role in tumor-specific apoptosis by REIC/Dkk-3

Abstract: We recently showed that overexpression of REIC/ Dickkopf-3 (Dkk-3), a tumor suppressor gene, induced apoptosis in a tumor cell-specific manner. The aim of the present study was to determine the mechanisms underlying the selective induction of apoptosis. At first, we found a mouse renal carcinoma cell line, RENCA, to be extremely sensitive to an adenovirus carrying REIC/Dkk-3 (Ad-REIC), and we showed that activation of c-Jun N-terminal kinase (JNK) was a critical step in cell death, i.e. a process similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…DKK3, a member of the DKK family, has been reported to be associated with the noncanonical Wnt pathway in various cancers (25)(26)(27)(28) and has also been reported to be involved in the canonical pathway in others (12,29). Several studies have indicated that DKK3 functions as a tumor suppressor for human cancer growth and is involved in apoptosis (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…DKK3, a member of the DKK family, has been reported to be associated with the noncanonical Wnt pathway in various cancers (25)(26)(27)(28) and has also been reported to be involved in the canonical pathway in others (12,29). Several studies have indicated that DKK3 functions as a tumor suppressor for human cancer growth and is involved in apoptosis (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5 In prostate cancer PC-3 cells, the overexpression of REIC/Dkk-3 activates JNK, reduces the Bcl-2 protein level, induces the mitochondrial translocation of Bax protein, releases cytochrome c into the cytoplasm, thus finally leading to apoptotic cell death. 1 This study first demonstrated that cleaved caspase-3 was involved in the Ad-REIC-induced apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The REIC gene is identical to Dickkopf-3 (Dkk-3) gene and REIC/Dkk-3 has been considered as a tumor suppressor gene to provide a new means of gene therapy for some of the human malignant tumors. The forced expression of REIC/Dkk-3, using a plasmid vector, inhibited cell growth in HeLa and liver cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…REIC/Dkk-3 expression is down-regulated in a broad range of cancer cell lines and clinical cancer materials (2)(3)(4)(5)(6)(7)(8)(9)(10). The expression of the human REIC/Dkk-3 gene is significantly down-regulated in human prostate cancer specimens in comparison to normal human prostate tissue at the protein level (5).…”
Section: Introductionmentioning
confidence: 99%